1999
DOI: 10.1149/1.1392621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenic Doping on Chemical Vapor Deposition of Titanium Silicide

Abstract: Titanium silicide (TiSi 2 ) has long been used in complementary metal oxide silicon (CMOS) integrated circuits because of its low resistivity and compatibility with standard processes. 1 With the scaling of device dimensions into the deep submicron regime, two problems related to the conventional self-aligned silicide (SALICIDE) process have emerged. The first problem is the so-called narrow-line effect which describes the difficulty in conversion of TiSi 2 from the high resistivity C49 phase into the low resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These results were consistent with the previous observations which indicate that higher deposition temperatures reduce consumption and that consumption mostly occurs during the initial stages of deposition. 10 Figure 4 also shows that the dependencies of the actual arsenic loss on temperature and time follow the same trends as those due to consumption, which suggests that the additional mechanisms must also be closely related to consumption. The injection of vacancies into the substrate during consumption is believed to be the reason for the enhanced arsenic diffusion, which is discussed in detail later in this paper.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…These results were consistent with the previous observations which indicate that higher deposition temperatures reduce consumption and that consumption mostly occurs during the initial stages of deposition. 10 Figure 4 also shows that the dependencies of the actual arsenic loss on temperature and time follow the same trends as those due to consumption, which suggests that the additional mechanisms must also be closely related to consumption. The injection of vacancies into the substrate during consumption is believed to be the reason for the enhanced arsenic diffusion, which is discussed in detail later in this paper.…”
Section: Resultsmentioning
confidence: 76%
“…A recent study from this laboratory explored selective CVD of TiSi 2 on heavily arsenicdoped substrates. 10 It was found that arsenic introduces a barrier to TiSi 2 nucleation and results in enhanced substrate consumption. It was also shown that arsenic displays a strong tendency to diffuse into TiSi 2 during deposition.…”
mentioning
confidence: 99%
“…TiSi 2 was the first used silicide [7]. However, its electrical resistance increased abruptly with the line width for narrow lines (below 0.25 mm) [8,9]. For CoSi 2 , it was found that this silicide consumed a relatively large amount of silicon resulting in a thick silicide layer [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, TiSi 2 is unsuitable for the nano-scale CMOS process because of its dependence on line width and its high temperature agglomeration [7,8]. CoSi 2 also has problems such as high temperature agglomeration, volume expansion, and the need for an excessive cleaning process to remove the native oxide [9].…”
Section: Introductionmentioning
confidence: 99%